Exosomal HSP60: a potentially useful biomarker for diagnosis, assessing prognosis, and monitoring response to treatment. (2nd September 2017) - Caruso Bavisotto, Celeste; Cappello, Francesco; Macario, Alberto J.L.; Conway de Macario, Everly; Logozzi, Mariantonia; Fais, Stefano; Campanella, Claudia
ABSTRACT: Introduction : Cell-to-cell communication is imperative for life and it is mediated by sending and receiving information via the secretion and subsequent receptor-mediated detection of biological molecules. Exosomes (EXs) secreted from cells to the extracellular environment play an important role in intercellular communication in normal and pathological conditions. Areas covered : New evidence indicates that tumor cells-derived EXs contribute to cancer progression through the modulation of tumor microenvironment. The exosomal heat shock protein 60 (HSP60) is very likely a key player in intercellular cross-talk, particularly during the progress of diseases, such as cancer. Many studies have focused on the extracellular roles played by HSP60 that pertain to cancer development and immune system stimulation. Our experimental data in vitro and in vivo demonstrated that HSP60 occurs on the surface of EXs secreted by tumour cells. Expert commentary : Exosomal HSP60 has great potential for clinical applications, as a 'liquid biopsy', including its use as biomarker for diagnostics, assessing prognosis, and monitoring disease progression and response to treatment, particularly in cancer.